IDENTIFIKASI KUTU PUTIH PADA TANAMAN PISANG KEPOK (Musa acuminata) DI BAKUNASE KECAMATAN KOTA RADJA, KOTA KUPANG - Febrianus Efantry; Rika Ludji; Agustina E Nahas; Yasinta L Kleden (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This research aims to identify mealybugs and to determine the symptoms of damage caused by mealybugs on Kepok banana plants in Bakunase Village, Kota Radja District, Kupang City. This research uses a survey method with direct observation techniques on banana plants. Data collection was carried out by directly observing banana plantations, then identified at the Plant Pest Laboratory, Faculty of Agriculture, Nusa Cendana University. The variables observed were the population of mealybugs found, the morphological characteristics of mealybugs, and the intensity of damage. The research results showed that the mealybug species found were Planococcus citri, Pseudococus jackbeardsleyi and Paracoccus marginatus. With the respective averages being Planococcus citri 20.5, Pseudococus jackbeardsleyi 18.62, Paracoccus marginatus 17.12. Symptoms of damage due to attacks caused by the three species of mealybugs are characterized by the skin of the fruit becoming dry and apart from that the fruit also becoming dirty and black in color. The intensity of damage increased every week with the highest percentage of damage occurring in the second week to the third week, namely 2.77%, and the lowest percentage of damage was in the seventh week to the eighth week, namely 0.1%.